A fatal case of congenital surfactant deficiency caused by ABCA 3 gene mutation in a newborn - Ghimire, Deen Dayalu; Joshi, Suchita (Nepalese Respiratory Journal, 2022)
Respiratory distress syndrome is a common cause for admission in neonatal intensive care unit and is predominant in preterm infants. Rarely, this can cause respiratory distress in full term infants. Here, we present a case of a full term baby without any other obvious cause for respiratory distress and transiently responding to surfactant administration, who eventually died at 1 month of age. As her elder sibling had also died following similar course of illness, congenital surfactant deficiency was suspected and blood sample for genetic testing was sent. This revealed ABCA 3 mutation as the cause of congenital surfactant deficiency.